Left ventricle dysfunction in patients with critical neonatal pulmonary stenosis: echocardiographic predictors. A single-center retrospective study - Carolina D’Anna; Alessio Franceschini; Micol Rebonato; Paolo Ciliberti; Claudia Esposito; Roberto Formigari; Maria Giulia Gagliardi; Paolo Guccione; Gianfranco Butera; Lorenzo Galletti; Marcello Chinali (PeerJ, 2022)
Background The aim of this study is to identify echocardiographic predictors of transient left ventricle dysfunction after pulmonary valve balloon dilatation (PVBD), in neonates with pulmonary valve stenosis (PVS) and atresia with intact septum (PAIVS) at birth. Methods The study includes patients admitted at the Bambino Gesù Children Hospital from January 2012 to January 2017. Clinical, echocardiographic and cardiac catheterization data before and after PVBD were retrospectively analyzed. Results Twenty-nine infants were included in the study (21 male and eight female). The median age was 5.8 ± 7.1 days. Eight patients developed transient LV dysfunction (three PAIVS and five PVS) and comparing data before and after the procedure, there was no difference in right ventricle geometrical and functional parameters except for evidence of at least moderate pulmonary valve regurgitation after PVBD. Conclusion Moderate to severe degree pulmonary valve regurgitation was significant associated to LV dysfunction (p < 0.05) in PVS and PAIVS patients.